Dampak Kepemilikan Faktor Produksi Terhadap Kesejahteraan Masyarakat Petani Padi di Desa Pasar Melintang Kec. Lubuk Pakam - Liscorpio G Lee Nainggolan (Yayasan Literasi Sains Indonesia, 2023)
As an agricultural country, attention to the welfare of farmers in Indonesia is considered very strategic. This study aims to find out how the impact of ownership of the factors of production of land area, labor, capital, and expertise on the welfare of the rice farming community in Pasar Melintang Village, Kec. Lubuk Pakam. This study uses primary data, namely data obtained from rice farming communities through observation and distribution of questionnaires, the number of samples used is 100 rice farmers in that location. To measure the level of welfare of the rice farming community, it is carried out using indicators of the level of welfare from the Central Statistics Agency (BPS), which consists of eight indicators, namely income, consumption, housing, housing facilities, health of family members, ease of accessing health services, educational facilities, educational facilities. transformation. In analyzing the magnitude of the influence of the independent variables on the dependent variable, multiple linear regression analysis models are used. The test results of the coefficient of determination show that all variables (X) can explain the welfare variable (Y) of 0.451 or 45.1% while the remaining 54.9% is influenced by other factors not explained in this study. Simultaneous testing (together) has a Sig value. (0.000) < 0.05, it can be concluded that land area, labor, capital and expertise simultaneously (together) affect the welfare of the rice farming community.